2019
DOI: 10.3390/ma12233971
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and Its Effects on Metallic Brackets and Wires: Does It Alter the Temperature and Bonding Efficacy of Orthodontic Devices?

Abstract: Magnetic resonance imaging (MRI) is a widely used diagnostic technique. Patients wearing orthodontic appliances are often requested to remove their appliances, even when the MRI exam involves anatomical areas far from mouth, in order to avoid heating of the metal and detachment of the appliance. The purpose of the present investigation was to measure and compare temperature changes and orthodontic appliances’ adhesion to enamel after different MRIs. A total of 220 orthodontic brackets were bonded on bovine inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…As such, it is important to reproduce these parameters in further randomized clinical trials and then compare the results with the present study. Moreover, other very common intra-oral situations, such as the presence of zirconia prosthetics, the demand for aesthetic ceramic brackets, or the influence of external conditions like magnetic resonance exposition, that have been reported to influence SBS could not be evaluated in our in vitro study [25][26][27][28]. However, further studies can be designed to check the behavior of the materials in these common clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is important to reproduce these parameters in further randomized clinical trials and then compare the results with the present study. Moreover, other very common intra-oral situations, such as the presence of zirconia prosthetics, the demand for aesthetic ceramic brackets, or the influence of external conditions like magnetic resonance exposition, that have been reported to influence SBS could not be evaluated in our in vitro study [25][26][27][28]. However, further studies can be designed to check the behavior of the materials in these common clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although these changes were statistically significant, they were clinically not relevant. Therefore, the researchers of the mentioned study concluded that these fixed orthodontic appliances presented a low risk with no difference between the 1.5 T and 3 T groups [ 12 ]. We found only one article in the literature which used a 7 T MRI machine for testing the heating effect of retainer wire, the results of which were indicative of only an irrelevant 1.5 °C increase during the study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Sfondrini examined 220 orthodontic appliances (brackets and wires) and demonstrated that there was no relevant debonding effect tested with the shear bond strength test and there were no significant differences between the different materials and sizes of wires [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…To date, no studies have evaluated the SBS of molar bands after MRI, but Sfondrini et al [ 9 ] have recently investigated the effects of MRI on orthodontic brackets by measuring the SBS. Values obtained under all conditions tested were clinically acceptable, consequently, this is in agreement with the present report.…”
Section: Discussionmentioning
confidence: 99%
“…Since clear guidelines are not available, orthodontists are interested in understanding the effects of orthodontic appliances on MRI to minimize the need for their removal [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%